CRIMINAL LIABILITY ANALYSIS FOR ILLEGAL TRADE IN PROTECTED WILDLIFE (KASONGAN PN DECISION NUMBER 48/PID.B/LH/2019/PN KSN) - Ifa Lorenza; Aristoteles; Hilyatul Asfia; Kiki Kristanto (RADJA PUBLIKA, 2026)
The illegal trade in protected wildlife constitutes a form of environmental crime that poses serious threats to biodiversity conservation and ecosystem balance. Indonesia, as a country with one of the highest levels of biodiversity in the world, faces significant challenges in enforcing the law against persistent wildlife trafficking practices. This study aims to analyze the legal framework and the application of criminal liability for perpetrators of illegal trade in protected wildlife, as reflected in the Decision of the Kasongan District Court Number 48/Pid.B/LH/2019/PN Ksn. The research employs a normative legal method using a statutory approach and a case approach. The findings indicate that the regulation of protected wildlife trade in Indonesia has been comprehensively established through Law Number 5 of 1990, reinforced by Law Number 32 of 2024, with Government Regulation Number 7 of 1999 serving as its implementing regulation. The analysis further shows that criminal liability is imposed on the offender on an individual basis, based on the fulfillment of criminal elements in the form of intentional trading of protected wildlife without the required authorization. However, the sentence imposed in the case is relatively lenient when compared to the maximum penalties specified by law. This situation reflects a gap between normative legal provisions and sentencing practices, which may undermine the effectiveness of law enforcement and the achievement of sustainable wildlife protection objectives.